Improving Students' Speaking Fluency By Using Direct Practice Of Speaking Day In School Environment At The First Year Of MAN 2 MADIUN 2007/2008 - Rohmatin, Lina (2008)
This research aims at describing the results of English Speaking Day and difficulty of English Speaking Day faced by the teacher and students'. This research is a descriptive qualitative research. The data are taken from (1) event; the learning speaking activities by "English Speaking Day" which focuses on the results of this program and the difficulties faced by the first students at MAN 2 MADIUN, (2) informant; the English teacher and the first year students. The writer collects the data by observing the speaking class, interviewing the teacher and the students, and analyzing the document. From the data analysis, the writer draws some conclusions the way to improve students' speaking fluency. First, the results of English Speaking Day faced by the students that consist of: (a) vocabulary is a central towards the language and critical importance to typical language learner, (b) pronunciation, a correct conversation can identify that our English is good because pronunciation is a first factor noticed by others, (c) grammar is language structure which every sentence has certain rule, (d) fluency in speaking and thinking needed much in communication. Second, the difficulties faced by the teacher are Quantity of the students in English Speaking Day, students' psychological factors and lack of fee. The last, the difficulties faced by the students are vocabulary mastery, pronunciation, grammar and anxiety.